Antioxidant Activity Analysis of Ethanol Extract from Melandean Leaves (Bridelia micrantha) Using the DPPH Assay - Bayani, Faizul; Rahayu, Lale Budi Hutami; Rahayu, Supiani; Huaida, Nurul; Yuliana, Depi; Hulyadi, Hulyadi; Gargazi, Gargazi (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The increasing global prevalence of oxidative stress-related diseases such as cardiovascular disease, diabetes, and neurodegenerative disorders underscores the importance of developing effective antioxidant strategies. In this study, samples of ethanol extract from Bridelia micrantha (Melandean) leaves were used which were then evaluated using the DPPH (2,2-diphenyl-1-picrylhydrazyl) test, a method that is widely known for assessing free radical scavenging activity. The ethanol extract sample was obtained through maceration with a yield of 15.84%. Based on the DPPH test, it shows that the extract has dose-dependent inhibition of DPPH radicals, with a maximum inhibition of 66.13% at a concentration of 25 ppm. The IC50 value, calculated from regression analysis, confirmed the antioxidant potential of the extract, although it was less effective than that of vitamin C, which was used as a positive control. These findings suggest that Bridelia micrantha leaves, rich in phytochemicals such as flavonoids, tannins, and saponins, have the potential as a source of natural antioxidants for managing oxidative stress-related health conditions.